Quantum Leap Dance Theatre of Harlem's long overture return to London - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Dance Theatre of Harlem. PALABRAS CLAVE: Dance Theatre of Harlem Company, Arthur Mitchell, New Bach, Twist, The Four Temperaments, George Balanchine.